VD_FINDINFO Jug / 2025 / 40 vom 12. Dezember 2024 - VD Tribunal cantonal (2024)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION, DÉCISION D'IRRECEVABILITÉ | 410 CPP (CH), 412 al. 1 CPP (CH), 412 al. 2 CPP (CH)